The Relationship Between Executive Compensation and Corporate Performance in Energy Companies Around the World - Zhang, Su (2020)
In modern society, more than half of the total consumption of all countries in the world is energy consumption. Human activities are heavily dependent on energy. And promoting the development of the energy industry is of great significance to the survival and development of people. However, the research focusing on executive compensation of energy companies is still insufficient. This paper studies the relationship between executive compensation and corporate performance of global energy companies. Data from 121 listed energy companies from 2010 to 2019 were collected for regression analysis. Executive compensation consists of cash compensation and equity incentives. Other determinants such as company size, gearing, equity concentration and number of committees are included in the research as control variables. The results show that in the energy industry, executive compensation has a significant positive impact on corporate performance, which is consistent with agency theory, tournament theory and social network theory. In addition, we found that cash incentives are more useful than equity incentives for senior executives. Therefore, we recommend that energy companies establish a reasonable compensation incentive system to promote further development. Besides, in the context of global energy shortage and environmental pollution, the development and use of new energy is an inevitable trend. Energy companies should accelerate the pace of innovate to achieve long-term development, which is conducive to both development of enterprises and the undertaking of social responsibility. Energy companies are suggested to link executive payment with corporate innovation, therefore, the value of the company could be further enhanced. Keywords: executive compensation, corporate performance, company size, equity concentration, corporate governance.